A case of Lhermitte-Duclos disease: the classical “tiger stripes” in magnetic resonance imaging - Sensusiati, Anggraini Dwi; Apriawan, Tedy; Fauziah, Dyah (Medical Journal of Indonesia, 2026)
Dysplastic gangliocytoma or Lhermitte-Duclos disease (LDD), is a rare benign cerebellar tumor often presenting with nonspecific symptoms such as intracranial hypertension, cerebellar dysfunction, or cranial nerve deficits, and associated with phacomatosis. The characteristic “tiger stripe” sign on magnetic resonance imaging (MRI) is highly suggestive of LDD, though nodular medulloblastoma remains an important differential diagnosis. We report a 51-year-old woman with arm and leg phacomatosis who presented with a right cerebellar hypodense lesion on computed tomography extending frontally. MRI demonstrated the hallmark “tiger stripe” appearance, and histopathology following surgery confirmed LDD. On follow-up, despite evidence of a recurrent mass on MRI, her cranial nerve paresis improved postoperatively. Imaging revealed hypointense striations on T1 and alternating linear hyperintensities on T2 sequences, obscuring the cerebellar folia, features that distinguish LDD from other cerebellar tumors. This case underscores the diagnostic value of MRI, emphasizing early recognition to prevent misdiagnosis and guide surgical planning.